A conceptual foundation for understanding musico-technological creativity. Issue 1 (22nd May 2012) - Slater, Mark; Martin, Adam
The point of departure for this article is the observation that increasing numbers of people are using technologies to create music. This rise in activity correlates directly with the proliferation of increasingly miniaturized music technologies which, in turn, implies an increasingly fluid level of mobility. As technologies get smaller and lighter, locations previously unusable for musico-technology creativity become available. We assert that the context of creativity (including sociocultural and local-architectural dimensions) is inextricably entwined with the nature of creativity. We set out a theoretical view that can trace and capture the relationship between the context and nature of creativity using an approach informed by phenomenology and critical realism. By understanding the essence of the invariant characteristics of musico-technological creativity, the connecting sinews between the more familiar, centralized enactments (recording a drum kit in a studio) and the less localized, less formalized enactments (making a track from scratch on the train platform with a mobile phone) can be drawn out.